AGROEPI: Technology solution for EPI use control on countryside - Fernanda Bergamo Calderari; Kimberli Terumy Sato (Revista Eletrônica Competências Digitais para Agricultura Familiar, 2015)
In agriculture, one of the concerns of landowners in managing their employees regards into ensuring the physical integrity of them, including the use of personal protective equipment (PPE) that are required to be delivered to employees. The objective of this paper is to provide a technological solution proposed to assist rural employers in control of the use of PPE. The AgroEPI software can be used through mobile devices and brings together features that can be applied to several types of crops, and its operation is supported by databases generated by inputting employees data. In this way, managers are able to monitor which employees are making use of PPE if there are any problems with the equipment, and whether to provide awareness training about the importance of using. Gathering and processing this information, managers may prevent possible law irregularities, preserving health and physical integrity of employees and reduce the risk of accidents that may cause financial losses and staff turnover.